Gender and self-selection into a competitive environment: are women more overconfident than men? - Lena Nekby; Peter Skogman Thoursie; Lars Vahtrik (Institute for the Study of Labor (IZA), 2007)
Using a large running race in Sweden, this study shows that there are male-dominated environments in which the selection of women who participate are more likely to be confident/competitive and that, within this group, performance improves equally for both genders.
urn:nbn:de:101:1-20080401366
Keywords: 330; Sport; Vertrauen; Wettbewerb; Persönlichkeitspsychologie; Soziale Beziehungen; Geschlecht; Schweden